MECHANICAL PROPERTIES OF WATERCRESS STALKS AT DIFFERENT POSITIONS - Zhoulong Lv; Kai Feng; Liangjun Li; Hong Miao; Shanwen Zhang (Engenharia Agrícola, 2024)
ABSTRACT Mechanised watercress harvesting involves clamping and cutting its stalks, which can result in their incomplete breaking and crushing. The harvest quality is directly affected by the force used to clamp and cut the watercress stalks. Therefore, studying the physical and mechanical properties of the stalks is important to accurately calculate the force that needs to be applied. Herein, the microstructure of watercress stalk sections with and without nodes was observed using scanning electron microscopy. Moreover, the basic physical properties, such as the total length, internode outer diameter, internode inner diameter and water content, of watercress stalks were measured. Additionally, the mechanical properties of watercress stalks at different positions were measured using four modes: tension, compression, shear and bending. Results revealed that watercress stalks with nodes exhibited a more pronounced medullary cavity and a greater number of internal vascular bundles. The lower section of the watercress stalks was considerably more resistant to mechanical stress than the rest of the stalk. Further, in terms of resisting load, the stalks with nodes were stronger than those without nodes. This study provides useful information for efficient watercress harvesting.